Butch queens up in pumps: Gender, performance, and ballroom culture in Detroit - Bailey, Marlon M. (University of Michigan Press, 2013)
Butch Queens Up in Pumps examine la culture Ballroom, dans laquelle les individus LGBT des centres-villes s'habillent, dansent et voguent pour concourir pour des prix et des trophées. Les participants sont affiliés à une maison, une structure familiale alternative généralement nommée d'après les créateurs de haute couture et apportant son soutien à cette communauté diversifiée. La riche ethnographie de performance à la première personne de Marlon M. Bailey sur la scène Ballroom de Détroit examine Ballroom comme une formation culturelle queer qui bouleverse les notions dominantes de genre, de sexualité, de parenté et de communauté.
Keywords: amériques; approches et analyses; arts; danse; discipline; identités LGBTQIA2+; performance; queer; régions géographiques; théâtre; états-unis

Queering the Crip or Cripping the Queer?: Intersections of Queer and Crip Identities in Solo Autobiographical Performance - Sandahl, Carrie (GLQ: A Journal of Lesbian and Gay Studies, 2003)
As the interdisciplinary field of disability studies develops its own theoretical paradigms, it necessarily borrows from various sources. Such borrowing means that disability scholars have not had to reinvent the wheel but have been able to build on the conceptual foundations of identity-based theories that have grown out of other interdisciplinary fields, such as gender studies and critical race studies. But disability studies offers as much to its predecessors as it borrows from them. This essay explores the productive reciprocity between queer theory and disability studies, queer identity and crip identity, queer activism and crip activism.
Keywords: EDI; LGBTQIA2+; approches et analyses; arts; capacitisme; care; corps; cours; crip; discipline; hétérosexisme; identités LGBTQIA2+; intersectionnalité; lit4700; militance; premier cycle; queer; ressource en ligne; santé; systèmes d'oppressions; thématiques; théâtre; études littéraires